Introducing the Digital Humanities in Ireland Landscape Report Dataset - Michelle Doran (Studi Irlandesi, 2022)
The UK-Ireland Digital Humanities Network was jointly funded in July 2020 by the Irish Research Council (IRC) and the UK Research and Innovation’s (UKRI) Arts and Humanities Research Council (AHRC) under the ground-breaking Collaboration in Digital Humanities Networking Grant Scheme. The joint aims of the Network were to: a) undertake research and consultation towards the implementation of a permanent UK-Ireland Digital Humanities Association; and b) to develop a clear roadmap for collaboration in the field between the two countries. An ancillary objective of the Irish Network members is to provide an up-to-date evaluation of the role and scope of Digital Humanities in Ireland, both past and present, to facilitate longer-term thinking about Digital Humanities so that we might optimise future developments in the field, including the nascent UK-Ireland Digital Humanities Association. To that end, the respective partners are developing a Digital Humanities in Ireland Landscape Report. The research informing the Landscape Report will be delivered in two phases. The initial phase took place between March and September 2021 and comprised the identification via desk research, collection and collation of data pertaining to Digital Humanities entities in Ireland. The second phase of the data gathering/collection exercise entails the presentation of the preliminary dataset to the wider Digital Humanities community for input and suggestions. To that end, we have created an Open Science Framework (OSF) repository. This contribution introduces the Digital Humanities in Ireland Landscape Report dataset, its methodology and primary sources and offers some preliminary observations and analysis. It concludes with some suggestions for potential use cases and further directions for the dataset.